A novel species of Euspondylus (Squamata: Gymnophthalmidae) from the Andes Mountains of central Peru - Doan, Tiffany M.; Adams, Grant (Zootaxa, 2015)
The South American gymnophthalmid genus Euspondylus is distributed from Venezuela through Peru, with its highest diversity occurring in Peru. Euspondylus paxcorpus sp. nov. is a new species from Junín, Peru possessing prefrontal scales and represented by 60 specimens. The new species differs from all other species by the combination of four supraoculars with supraocular/supraciliary fusion, 5–7 occipitals, a single palpebral scale, five supralabials and infralabials, quadrangular dorsal scales with low keels arranged in transverse series only, 40–45 in a longitudinal count and 22–28 in a transverse count, 12 rows of ventrals in a transverse count and 23–25 in a longitudinal count, and no sexual dimorphism in coloration. The discovery of E. paxcorpus increases the known number of Euspondylus species to 13. Because the coloration patterns of the specimens were greatly different after preservation in alcohol, caution should be used when identifying Euspondylus species from museum specimens.